PENGARUH STRES KERJA, BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. MANDIRI TRI MAKMUR, BADUNG, BALI - I Gusti Komang Rai Dijaya; Ni Nyoman Suryani; Sapta Rini Widyawati (VALUES, 2021)
Human resources are part of the driving force of a company that has the potential to develop and actively encourages productivity in meeting company goals. Efforts to improve employee performance by paying attention to the problem of work stress, which is a condition where there is a pressure that affects the workforce. In addition, workload greatly affects labor productivity and efficiency. The work environment is also something that cannot be overlooked by the company because it will have an impact on the performance of the employees which affects the company. Employee performance refers to how an employee behaves in the workplace and how well an employee does the assigned task / job. This study aims to determine the effect of work stress, workload and environment on employee performance at PT. Mandiri Tri Makmur, Badung, Bali. The population in this study were employees of PT. Mandiri Tri Makmur, Badung, Bali with 100 employees. The sample of this study used the Slovin formula as many as 80 employees. The data analysis technique used is multiple linear regression analysis and multiple correlation analysis. In addition, in this research, instrument test, classical assumption test, which includes normality test, multicollinearity test and heteroscedasticity test were also carried out. The test results show that Work Stress and Workload have a negative and significant effect on Employee Performance at PT. Mandiri Tri Makmur, Badung, Bali. Meanwhile, the work environment has a positive and significant effect on employee performance at PT. Mandiri Tri Makmur, Badung, Bali. Together, Work Stress, Workload and Work Environment have a significant effect on Employee Performance at PT. Mandiri Tri Makmur, Badung, Bali.